Lipidomics analysis (SQDG) from water bottle samples in and around a cyclonic eddy during METEOR cruise M156, off Mauritania - Kevin W Becker; Quentin Devresse; Xavier Prieto-Mollar; Kai-Uwe Hinrichs; Anja Engel (PANGAEA, 2025)
This dataset includes lipidomics data over the surface mixed layer (0-35 m depth) of eleven stations with five of them inside or in the vicinity of a mesoscale cyclonic eddy that formed off Mauritania along a 900 km zonal corridor between Mauritania and the Cabo Verde islands in the eastern Tropical North Atlantic during the M156 cruise on the RV Meteor from July 3rd to August 1st 2019. Lipid samples were collected onto 0.22 μm Durapore filters (Millipore) and immediately flash-frozen and stored at -80 °C until processing. Extraction was performed using a modified Bligh and Dyer (Bligh and Dyer, 1959; https://doi.org/10.1139/o59-099) method described in Popendorf et al. (2013; https://doi.org/10.1007/s11745-012-3748-0). Lipid extracts were analyzed by HPLC-ESI-MS/MS on a Bruker maXis Ultra-High Resolution quadrupole time-of-flight tandem mass spectrometer (Bruker Daltonik, Bremen, Germany) equipped with an ESI ion source operating in positive mode. The HPLC-ESI-MS method is described in Wörmer et al., 2013 (https://doi.org/10.1016/j.orggeochem.2013.03.004). Lipids were identified by retention time as well as accurate molecular mass and isotope pattern match of proposed sum formulas in full scan mode and MS/MS fragment spectra. Lipid identities are resolved only to the level of lipid species, i.e., the sum of the properties of the substituents at both the sn-1 and sn-2 positions. After identification, quantification of analytes was performed using a series of standard curves, followed by normalization to concentration of an internal standard.
In: Becker, KW et al. (2025): Lipidomics analysis from water bottle samples in and around a cyclonic eddy during METEOR cruise M156, off Mauritania [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974978